The impact of COVID-19 on the delivery of interprofessional education: it's not all bad news. (2nd December 2021) - Wetzlmair, Lisa-Christin; Kitema, Gatera Fiston; O'Carroll, Veronica; El-Awaisi, Alla; Power, Alison; Owens, Melissa; Park, Vikki; McKinley, Mairi; Anderson, Elizabeth S; Loder-Fink, Brigitte
Abstract : During the COVID-19 outbreak, most face-to-face teaching and practice-based learning placements were suspended. Universities provided ongoing health and social care education, including interprofessional education, using online technology. Focusing on changes in the delivery of interprofessional education, this second article in a series on interprofessional education provides an international perspective through facilitators' case reports. It considers the key factors that enabled a rapid shift from face-to-face to online interprofessional education, and the key aspects that had to change. The significant changes reported from literature and case reports reflect on remote and online learning, the duration of education sessions, individual and team learning aspects and facilitation skills.